Effects of scanning strategies on residual stress and deformation by high-power direct energy deposition: Island size and laser jump strategy between islands. (March 2022) - Wang, Jingsheng; Zhang, Jiajia; Liu, Guangtao; Liang, Lvjie; Yang, Guang; Huang, Anguo; Pang, Shengyong
Abstract: The path-dependent residual stress and deformation are two critical defects of the parts fabricated by direct energy deposition (DED). The optimal design of the scanning strategy is an important method for controlling the residual stress and deformation. In this paper, a thermo-mechanical finite element model based on the modified flash heat method was developed to simulate the high-power DED process. The effects of the island size and the laser jump strategy between islands were investigated on the residual stress and deformation in the high-power DED component. The dependence of residual deformation on the laser jump strategy between islands was discussed. An evaluation method for the laser jump strategy was proposed. Finally, we carried out experiments for the validation. The results show that the z-direction maximum residual deformation decreases by 17.3%. The ratio of the area with high residual von Mises stress decreases from 93.1% to 5.1% when the island size decreases from 160 mm to 20 mm. We found that different laser jump strategies between islands lead to significant differences in residual deformation. Increasing the laser jump distance between islands plays a vital role in reducing the residual deformation. The dual-diagonal symmetry pattern and the "least" heat influence pattern lead to minimum residual deformation. The superposition and offset of the deformation caused by the mechanical interaction between islands have a remarkable effect on the history of the deformation in the DED process. The proposed evaluation method is reliable for designing or optimizing the laser jump strategy between islands. The optimal design idea of the laser jump strategy between islands is to adopt the large laser jump distance between islands while reducing the number of adjacent islands when depositing a new island. This work provides important insights for the scanning path planning of large parts built by high-power DED.